Counselling Psychology: A Discipline - Friesen, John D. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article is a beginning step in the process of defining counselling psychology as a discipline. The following areas are examined: (1) the history of the emergence of disciplines, (2) the process fields of study move through in becoming disciplines, (3) the status of counselling psychology in relationship to the criteria of a discipline, and (4) the domain of psychological knowledge included in the discipline of counselling psychology